PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL TERHADAP PRESTASI AKADEMIK - Adhi Prastistha Silen (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2014)
This study aimed to analyze the influence of intellectual, spiritual intelligence and emotional intelligence on learning outcomes in cadets Semarang Merchant Marine Polytechnic. Types of research used in this study using explanatory research methods. The population in this study were all cadets Semarang Merchant Marine Polytechnic semester of four (4) academic year 2012/2013 amounted to 350 cadets. The sampling technique used in this study were stratified proportional sampling. Samples taken by 78 cadets. Analysis tool used is multiple linear regression.Based on this study concluded: There is a positive and significant effect between intellectual intelligence on learning outcomes. There is positive and significant correlation between emotional intelligence to the study results. There is positive and significant correlation between spiritual intelligence on learning outcomes Keywords: Intellectual Intelligence, Spiritual Intelligence, Emotional Intelligence, Learning Outcomes